Evaluation of effective anti-tumarogenic dose of ethanolic leaves extract of Moringa oleifera Lam. in Ehrlich ascites carcinoma bearing mice - B., Ramanath; John, Abhay (International Journal of Research in Medical Sciences, 2022)
Background: To evaluate the optimum protective and curative antitumarogenic dose of the ethanolic leaves extract of Moringa oleifera Lam (ELMO). variety against Ehrlich ascetic carcinoma (EAC) cells. Methods: The protective and curative antitumor activity of ELMO was evaluated against the EAC tumor model. The activity was assessed using survival time and increase in life span. Results: Oral administration of all the doses of treated ELMO shown significantly increased in mean survival time and percent of life span, in that 500 mg/kg body wt. shown highest significance. Conclusions: ELMO treated 500 mg/kg body wt. possesses showed antitumor activity.